Persaingan usaha di era digital: tantangan dan penegakan hukum pertumbuhan e-commerce di indonesia - Ahadia, Zahro Ahadia (Maliki Interdisciplinary Journal, 2025)
This research discusses the dynamics of business competition in digital era, especially in the context of the growth of e-commerce in Indonesia. However, this growth also causes challenges in business competition, including anti-competition, monopoly, and unequal market access. This research aims to examine business competition in Indonesian e-commerce, identify challenges for business actors, analyze the effectiveness of policies and law enforcement to create a fair and competitive business environment. This research uses a qualitative approach to determine the dynamics of business competition in the digital era, especially in the context of the growth of e-commerce in Indonesia. The research method used includes literature studies by collecting information from various sources, including academic journals, books, research reports and news articles relevant to the topic of business competition and e-commerce. And also uses research methods to analyze various legal documents related to business competition and e-commerce in Indonesia including laws, government regulations, and guidelines issued by relevant authorities such as the Business Competition Supervisory Commission (KPPU). The research results show the challenges faced by e-commerce in Indonesia, such as digital monopoly, predatory pricing, lock-in policies by large platforms, and vertical integration by companies. Law enforcement needs to be adapted to deal with changing market dynamics. KPPU has an important role in ensuring healthy and fair competition.